2011
DOI: 10.3858/emm.2011.43.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Microglial P2X7receptor expression is accompanied by neuronal damage in the cerebral cortex of the APPswe/PS1dE9 mouse model of Alzheimer's disease

Abstract: The possibility that P2X7 receptor (P2X7R) expression in microglia would mediate neuronal damage via reactive oxygen species (ROS) production was examined in the APPswe/PS1dE9 mouse model of Alzheimer's disease (AD). P2X 7 R was predominantly expressed in CD11b-immunopositive microglia from 3 months of age before Aβ plaque formation. In addition, gp91 phox , a catalytic subunit of NADPH oxidase, and ethidium fluorescence were detected in P2X 7 R-positive microglial cells of animals at 6 months of age, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
68
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 49 publications
6
68
0
4
Order By: Relevance
“…Furthermore, previous studies indicated that an altered activity of the purinergic P2X7 receptor mediates the pro-inflammatory processes in a transgenic AD model and in brains of AD patients [46,49,59]. The observation that Aβ may cause ATP release from microglia, and that P2X7 receptor is an obligate participant in microglia activation by Aβ, put the role of ATP and P2 receptors as a key event in neurodegeneration [42,63].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies indicated that an altered activity of the purinergic P2X7 receptor mediates the pro-inflammatory processes in a transgenic AD model and in brains of AD patients [46,49,59]. The observation that Aβ may cause ATP release from microglia, and that P2X7 receptor is an obligate participant in microglia activation by Aβ, put the role of ATP and P2 receptors as a key event in neurodegeneration [42,63].…”
Section: Discussionmentioning
confidence: 99%
“…В клетках микроглии P2X7 рецепторы регулируют клю-чевые события их активации при воспалении, например секрецию цитокинов, продукцию свободных радикалов, в т.ч. при хронической нейродегенерации [12].…”
Section: цитокинпродуцирующая активность клеток при нейровоспалении иunclassified
“…Alterações decorrentes do acúmulo de amiloide O acúmulo de βA provoca disfunção respiratória e bioenergética por diminuição de piruvato desidrogenase, citocromo oxidase e superóxido dismutase 2 (SOD-2) 36,37 e aumento de cálcio intracelular após desestabilização do potencial de membrana mitocondrial; 27 aceleração da senescência de células progenitoras neurais do hipocampo; 38 ativação do processo inflamatório com consequente liberação de citocinas 13 e ativação microglial, 29,38,39 com todos esses caminhos culminando no aumento de EROs mitocondriais, que possivelmente estariam envolvidos na formação das placas de amiloide. 36 As EROs promovem a regulação positiva do gene regulador da calcineurina, que inibe a proteína de atuar como fosfatase da proteína tau, resultando em hiperfosforilação da proteína tau e consequente formação de emaranhados neurofibrilares envolvidos na patologia da doença de Alzheimer (DA), causando falha sináptica e apoptose.…”
unclassified
“…37 A ativação microglial libera ATP, que ativa o canal responsável pelo influxo de Ca 2+ , ocorrendo oxidação de NADPH e produção de EROs, resultando em dano neuronal e disfunção cerebrovascular. 38 O estímulo ocorre mais fortemente a partir da forma fibrilar do amiloide, mas a forma solúvel também é capaz de provocar estímulos, demonstrando que o estresse oxidativo ocorre mesmo no início da DA. 29,38 O dano promovido pela ativação microglial ocorre principalmente pela produção de citocinas, quimiocinas e EROs, que também participam da senescên-cia celular 39,40 e que podem debilitar a via TGFβ1-Smad3, envolvida com a modulação da ativação da micróglia, provocando maior produção de agentes oxidantes.…”
unclassified